2016 Elijah High Altitude Balloon Launch Team Summer Proceedings Report - Faltersack, Brianna; Maraccini, Jared; Petrie, Jordan; Rasmussen, Tyler (Proceedings of the Wisconsin Space Conference, 2017)
The 2016 Wisconsin Space Grant Consortium Elijah High Altitude Balloon Launch Team was comprised of two students from Milwaukee School of Engineering, one student from University of Wisconsin â€“ Fox Valley, and one student from Carthage College. This year, the majority of the students involved were discovering the balloon launch experience for the first time. The 2016 Elijah Balloon Launch Team held a meeting for the new members to learn how all of the equipment worked through a practice run using the tools in a trial.The first launch planned was cancelled, and was postponed to the next weekend. This launch was successful, reaching a peak altitude of 31,021m.Â 